2012
DOI: 10.1016/j.febslet.2012.06.048
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐145 suppresses mouse granulosa cell proliferation by targeting activin receptor IB

Abstract: a b s t r a c tMicroRNAs (miRNAs) are a class of 21-to 25-nucleotide non-coding RNAs, some of which are important gene regulators involved in folliculogenesis. In this study, we used CCK-8, real-time PCR and Western blot assays to demonstrate that miR-145 inhibits mouse granulosa cell (mGC) proliferation. Combined with the results of luciferase reporter assays that studied the 3 0 -untranslated region of ACVRIB mRNA, these assays identified ACVRIB as a direct target of miR-145. The ectopic expression of miR-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 43 publications
2
58
0
1
Order By: Relevance
“…), and miR-99a (EDF1, IGFBP2, etc.) were predicted in this study, and these have already been validated and reported as ovarian function-related genes (Hossain et al, 2009;Hossain et al, 2012b;Yan et al, 2012). One previous study has demonstrated that miR-125b, miR-145, and miR-99a were expressed at significantly higher levels in the ovaries of pregnant goats compared to non-pregnant goats (Zhang et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…), and miR-99a (EDF1, IGFBP2, etc.) were predicted in this study, and these have already been validated and reported as ovarian function-related genes (Hossain et al, 2009;Hossain et al, 2012b;Yan et al, 2012). One previous study has demonstrated that miR-125b, miR-145, and miR-99a were expressed at significantly higher levels in the ovaries of pregnant goats compared to non-pregnant goats (Zhang et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…Similarly, another study reported that treatment of cultured bovine granulosa cells with forskolin (an adenylate cyclase agonist) to promote luteinisation was followed by a decrease in the levels of miR-125b and miR-145 (McBride et al, 2012). Additionally, Yan et al (2012) reported attenuation of activin induced proliferation of mouse granulosa cells by miR-145 targeting ActRIB. Therefore, miR-125b, miR-145, and miR-99a may play a specific role in the regulation of ovarian function and mammalian reproduction.…”
Section: Discussionmentioning
confidence: 89%
“…The expression of the second activin type II receptor, ActRIIB, is controlled by five miRNAs in the context of normal kidney homeostasis, whereas kidney neoplasia in young children is characterized by down-regulation of miR-141, miR-192, miR-194, miR-200c, and miR-215, and consequent up-regulation of ActRIIB in the developing nephroblastomas (Senanayake et al 2012). The expression of activin/nodal type I receptors ActRIB/ALK-4 and ActRIC/ALK-7 is also negatively regulated by miRNAs; in normal ovarian granulosa cells, ALK-4 mRNA is targeted by miR-145, which controls cell proliferation (Yan et al 2012). During erythropoiesis, the ALK-4 mRNA is targeted by miR-24; ALK-4 down-regulation is required so that early stages of erythroid cell differentiation can progress .…”
Section: Control Of Tgf-b Receptor Expression By Micrornasmentioning
confidence: 99%
“…Several studies have already reported effects of specific miRNAs on different aspects of granulosa cell function , including steroidogenesis (Yao et al 2010, Xu et al 2011, Yin et al 2012, Dai et al 2013, proliferation (Yao et al 2010, Yan et al 2012, Dai et al 2013, survival (Carletti et al 2010, Yang et al 2012, terminal differentiation (Kitahara et al 2013), and cumulus expansion (Yao et al 2014). With a few exceptions (Carletti et al 2010, Kitahara et al 2013, most evidence on follicular roles of miRNAs has been obtained using cultured cells, particularly rodent cells, and in some cases actual changes in the expression of these miRNAs during follicle development have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%